2020
DOI: 10.3758/s13420-019-00408-2
|View full text |Cite
|
Sign up to set email alerts
|

Learning is negatively associated with strength of left/right paw preference in wild grey squirrels (Sciurus carolinensis)

Abstract: Cerebral laterality, via hemispheric specialisation, has been evidenced across the animal kingdom and linked to cognitive performance in a number of species. Previously it has been suggested that cognitive processing is more efficient in brains with stronger hemispheric differences in processing, which may be the key fitness benefit driving the evolution of laterality. However, evidence supporting a positive association between cognitive performance and lateralization is mixed: data from studies of fish and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, the association between a strong manifestation of cerebral lateralization and fitness benefits appears to be not that straightforward. For example, in goldbelly topminnows, Girardinus falcatus , non‐lateralized fish outperform lateralized ones in some visually guided spatial tasks (Dadda et al, 2009), and in wild gray squirrels, Sciurus carolinensis , a negative relationship between the strength of motor lateralization and learning speed was found (Leaver et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between a strong manifestation of cerebral lateralization and fitness benefits appears to be not that straightforward. For example, in goldbelly topminnows, Girardinus falcatus , non‐lateralized fish outperform lateralized ones in some visually guided spatial tasks (Dadda et al, 2009), and in wild gray squirrels, Sciurus carolinensis , a negative relationship between the strength of motor lateralization and learning speed was found (Leaver et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that lateralization may increase cognition through enhanced processing efficiency . Behavioral laterality is linked to enhanced learning abilities in species of fish and birds Sovrano et al, 2005), although some evidence suggests the reverse may be true in mammals (Leaver et al, 2020). Behavioral lateralization has been proposed as advantageous for coping with multiple stimuli from different directions, in species in which both visual fields are partly separated, or when coping with different tasks each represented in a different hemisphere.…”
Section: Introductionmentioning
confidence: 99%